Dynamics of onion selling prices in lesong village power Islamic supply perspective: Study on Onion Farmers in Lesong Daya Pamekasan Village - Mujibur Rahman; Muchammad Athoillah; Lilik Rahmawai (Universitas Darussalam Gontor, 2023)
The dynamics of onion selling prices in lesong daya village are quite diverse and varied and erratic from day to day month to month and so on. As a result of the changes that do not make the offer of shallots also not menetu and varied. The purpose of this study was to outline the impact of prices on onion supply with a study in lesong daya batu marmar village pamekasan district. The method used in this study is to use a descriptive qualitative approach, namely by conducting interview stages, documentation and field observations, to find out the number of offers, behavior and market performance. The results showed that there was a dynamic price change starting from July 2022, namely 42,500, August 55,000, September 32,500, and October 30,000 based on the price change having a direct impact on the supply that occurred. In addition to erratic price changes in market prices, the onion supply factor is also mediated by several factors, including (1) predictions of the production time or planting period of onions of farmers outside the Madura island area (2) the community will tend to be motivated to other onion farmers who have managed to get maximum profits (3) the onion planting period starts from the initial planting to the harvest period usually at least within a period of two months. So farmers assume that in small quantities or many seeds that they plant will take the same harvest time as well. (4) the amount of production to be offered will increase if the available seeds are priced cheaper at normal prices (5) weather changes are also a factor for the level of supply.